PROVISION OF LABOR PROTECTION AND ANALYSIS OF INJURIES OF ACTIVE PARTICIPANTS - Shovkiddin, Narziev; Elleonora, Yusupxodjaeva; Nargiza, Xolmatova; Surayyo, Abduraxmanova; Pulat, Shokirov (The journal of contemporary issues in business and government, 2021)
In this article, a general analysis of the causes of injury to the human body through the factors of Organization of production and the protection of labor during the organization of an active movement, as well as active movement and constant physical loads, an analysis of the causes of the injury of athletes engaged in the activity of the body, the impact.